Self Driving Car Using Deep Neural Networks - S, Sharmila; S, Shivaswaroop; M, Sudhakar; SV, Tejashwini; SA, Rajshekhar (International Journal of Computer Sciences and Engineering, 2025)
Automation has a wide role in the current generation which can be deployed into cars making them drive on their own by considering the surrounding environment as input parameters. Detection of lanes using canny edge lane detection algorithm helps to detect lanes and ensure the drivable space and have clear information of lane in which the car is moving. Deep Neural Networks helps in deciding the action to be performed by the car (forward, reverse, right, left, stop, and park). This paper covers motion control, path detection and obstacle detection. The results have been achieved by the implementation of Canny Edge Detection Algorithm, Deep Neural Networks Techniques.